Dream : the life and legacy of Hakeem Olajuwon - Fader, Mirin (2024)
"It's now the norm for NBA and collegiate teams to have international players dotting their rosters. The Olympics are no longer a gimme for Team USA. Both via fans streaming from all over the globe and leagues starting in countries throughout the world, the international presence of the game of basketball is a force to be reckoned with. That all started with Hakeem "the Dream" Olajuwon. "Dream," for short. He was the first international player to win the MVP, which is hard to believe now considering the last time an American born player won it was four years ago. Award-winning hoops journalist Mirin Fader explores this phenomenal shift through the lens of what Olajuwon accomplished throughout the 1980s and 90s. Dream ignites nostalgia for Phi Slama Jama and "the Dream Shake," while also exploring the profound influence of Olajuwon's Muslim faith on his approach to life and basketball, and how his devotion to his faith inspired generations of Muslim people around the world. Olajuwon's ongoing work with NBA Africa, his status as an international ambassador for the game, and his consultations with today's brightest stars, from LeBron James to Giannis Antetokounmpo, brings the story right up to the present moment, and beyond. Synthesizing hundreds of interviews and in-depth research, Fader provides the definitive biography of Olajuwon as well as a crucial understanding of his pivotal impact on the ever-shifting game"--
King -- Center -- Yommy -- Ticket -- Akeem -- Moses -- Slama -- Next -- Towers -- Different -- Shake -- Pride -- Darkness -- Found -- Perspective -- Clutch -- Ring -- Discipline -- Heart -- Citizen -- Business -- Toronto -- Ambassador -- Mentor.
Includes bibliographical references and index.
Keywords: Olajuwon, Hakeem, -- 1963-; Basketball players -- United States -- Biography; Nigerian Americans -- Biography